2020
DOI: 10.1007/jhep08(2020)039
|View full text |Cite
|
Sign up to set email alerts
|

On-shell electroweak sector and the Higgs mechanism

Abstract: We describe a new approach towards the development of an entirely on-shell description of the bosonic electroweak sector of the Standard Model and the Higgs mechanism. We write down on-shell three particle amplitudes consistent with Poincaré invariance and little group covariance. Tree-level, four particle amplitudes are determined by demanding consistent factorization on all poles and correct UV behaviour. We present expressions for these 2 → 2 scattering amplitudes using massive spinor helicity variables. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 40 publications
(50 reference statements)
0
39
0
5
Order By: Relevance
“…[41][42][43][44][45][46][47]). They have also been used as a convenient means for classifying interactions in EFTs such as the SMEFT [48][49][50][51][52]. In addition, general proper-JHEP10(2020)211 ties of the S-matrix, such as unitarity, causality and analyticity have been used to constrain Wilson coefficients of EFTs [53], including the SMEFT [54,55].…”
Section: Jhep10(2020)211mentioning
confidence: 99%
“…[41][42][43][44][45][46][47]). They have also been used as a convenient means for classifying interactions in EFTs such as the SMEFT [48][49][50][51][52]. In addition, general proper-JHEP10(2020)211 ties of the S-matrix, such as unitarity, causality and analyticity have been used to constrain Wilson coefficients of EFTs [53], including the SMEFT [54,55].…”
Section: Jhep10(2020)211mentioning
confidence: 99%
“…Unitarity arguments indicated that the theory of electroweak interactions is incomplete without a Higgs sector at or below the TeV scale. It was established in the 1970s that unitarity of amplitudes at high energy requires the theory to be a spontaneously broken gauge theory [1][2][3][4] (see [5][6][7] for a modern approach). Lee, Quigg, and Thacker [8,9] turned this into a quantitative constraint, showing that tree-level unitarity of longitudinal vector boson scattering could be used to give a bound on the energy scale of the Higgs sector (see also refs.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] for recent reviews), it seems much more natural to directly treat amplitudes as a description of the EFT, which are equivalent to the Wilson coefficients of the higher dimensional operators in the Lagrangian. Recent efforts have been made in parameterizing the Standard Model (SM) and its effective field theory (SMEFT) with on-shell amplitudes [26][27][28][29][30][31][32][33][34]. While the conventional parameterization, obtained by adding higher dimensional operators to the SM Lagrangian [35,36], still offers the most complete and practical description of the SMEFT, the on-shell approach does have certain advantages.…”
Section: Jhep03(2021)149mentioning
confidence: 99%